تأثير وسيلة بطاقة الدومينو على ترقية مهارة الكتابة لطلاب الصف السابع من المدرسة المتوسطة الحكومية 2 باجيران لامونجان - Finurika, Isna; Khoirunnisa’, Wardah; 'Ilma, Rahma Milladunna (Funun Arabiyyah: Journal of Arabic Education and Literature, 2025)
An Arabic language teacher at the Second State Junior High School of Bajiran usually uses lectures and exercises in teaching. However, sometimes they are unable to accommodate the diversity of students’ learning styles. This affects the decline in students’ enthusiasm and active participation in the learning process. Due to this problem, the researcher was encouraged to innovate in the learning process by applying an interactive and enjoyable teaching medium, namely the domino card method, to improve students’ Arabic writing skills. The problem in this study lies in how to apply the domino card method to enhance Arabic learning and to what extent this method affects students’ creativity. This research is a quantitative study with an experimental design, aiming to identify more effective learning by conducting an experiment using the domino card method in improving students’ Arabic writing. The research instruments used were tests, interviews, observations, and documentation. The data analysis technique employed the dependent t-test formula. The results of this study showed the effect of applying the domino card method in improving writing skills, as evidenced by the results of data analysis using a paired sample t-test, where the calculated t-value (t = 8.175) was greater than the table t-value (t = 2.032). It was proven that the application of the domino card method was able to increase students’ motivation and enthusiasm for learning. The engaging learning activities had a positive impact on improving writing skills (maharah al-kitābah).